Effects of Autoclaving, Addition of Sodium Hydroxide and Their Combination on Protein Content and in vitro Digestibility of Chicken Feathers - Al-Souti , Ahmed; Gallardo, Wenresti; Claereboudt, Micheli; Mahgoub, Osman (International Journal of Poultry Science, 2018)
Objective: The aim of this study was to determine the effects of NaOH addition, autoclaving and their combination on the protein and pepsin digestibility of chicken feathers. Methodology: The first experiment consisted of the following treatments: (1) The 2 h treatment with 1.0 M of NaOH, (2) The 12 h treatment with 1.0 M of NaOH, (3) The 24 h treatment with 1.0 M of NaOH and (4) Control, consisting of raw feathers incubated with only 100 mL of distilled water for 24 h at 37°C. The second experiment consisted of the following treatments: (1) Raw chicken feathers autoclaved at 2.5*105 Pa, at a temperature of 121°C for 30 min and (2) Raw chicken feathers soaked in 0.5% NaOH solution for 24 h, followed by autoclaving at 2.5*105 Pa and 121°C for 30 min. Results: The prolonged treatment (24 and 12 h) with NaOH improved feather solubility but resulted in lower protein retention, whereas the addition of NaOH followed by autoclaving resulted in higher protein content and increased in vitro pepsin digestibility. Conclusion:The addition of NaOH followed by autoclaving is recommended as a treatment for processing of chicken feathers.